A Fair Barbarian - Burnett, Frances Hodgson (Saga Egmont, 2021)
American heiress Octavia Bassett arrives in a sleepy English town to visit her aunt Belinda. She’s extremely wealthy, privileged and independent, which doesn’t go over well with the locals. Her arrival sets tongues wagging and ruffles feathers of the very conservative and traditional residents. Indifferent to the impression she creates, Octavia befriends Lucia Gaston, the meek granddaughter of the village matriarch, Lady Theobald.More friction arise as Lucia’s intended, Captain Barold, proposes to Octavia. She turns him down flat and leaves him dumbfounded. Meanwhile, Lucia, inspired by her friend’s independence falls in love with Mr. Burmistone, a mill owner her grandmother frowns upon.Then Octavia’s father and former fiancé arrive in town causing even more commotion among the locals.